2011
DOI: 10.1177/1352458511420598
|View full text |Cite
|
Sign up to set email alerts
|

Which walking capacity tests to use in multiple sclerosis? A multicentre study providing the basis for a core set

Abstract: A single short test format at fastest speed accurately describes an MS patient's general walking capacity. For intervention studies, a long test is to be considered. We propose the Timed 25-Foot Walk and 2-Minute Walk Test as standards. Further research on responsiveness is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 41 publications
(54 reference statements)
5
115
0
Order By: Relevance
“…dynamic vs. static start, normal speed vs. fastest speed, use of walking aids) and these differences in the format of the tests influenced the outcome. [9][10][11] Only one patient-based (i.e. subjective) measure of walking disability was identified in the search, which was the 12-item MS Walking Scale (MSWS-12; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…dynamic vs. static start, normal speed vs. fastest speed, use of walking aids) and these differences in the format of the tests influenced the outcome. [9][10][11] Only one patient-based (i.e. subjective) measure of walking disability was identified in the search, which was the 12-item MS Walking Scale (MSWS-12; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Walking assessments discriminated between MS patients and healthy controls based on walking speed (T25FW, 10MTW and 100MTW) 18,20 and walking distance (6mWT) [21][22][23] and between MS patients with different levels of disability based on the EDSS. 1,9,14,23 The T25FW time and 2mWT and 6mWT distance differed between MS patients with mild disability (EDSS 1.5-4.0) and those with moderate disability (EDSS 4.5-6.5). 1 Another study showed differences in 6mWT distance between MS patients with mild (EDSS 0-2.5), moderate (EDSS 3.0-4.0), or severe disability (EDSS 4.5-6.5; p = 0.05).…”
Section: Validitymentioning
confidence: 99%
“…15,16 The test is valid and reliable with negligible practice effects [17][18][19] and requires a minimum of equipment, time, and space; it is therefore of practical use in clinical research settings. 20,21 A change of 20% has been considered both reliable and clinically meaningful. [22][23][24][25][26] A key secondary outcome in both trials was evaluation of walking from the patient's perspective using the MSWS-12, 14 a clinically validated, patient-reported measure that assesses the impact of MS on walking ability, with a higher score indicating greater difficulty walking.…”
mentioning
confidence: 99%
“…The feasibility and benefit of collaborative networks in MS have been demonstrated in recent years by prospective data collection [12][13][14] in the European Rehabilitation in Multiple Sclerosis (RIMS) network (www. eurims.org).…”
mentioning
confidence: 99%
“…These collaborations have led to documentation of the psychometric properties of walking capacity tests 12 and have affected standardization in clinical practice in this domain. 13 The large sample size achieved allowed analyses to be performed in subgroups with different disabilities and MS types.…”
mentioning
confidence: 99%